May Measurement Month 2017: Results from Taiwan—East Asia. (24th April 2019) - Lin, Hung-Ju; Pan, Heng-Yu; Kobeissi, Elsa; Beaney, Thomas; Poulter, Neil R; Chen, Wen-Jone; Wang, Tzung-Dau
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programs worldwide. Given the consistent 30% unawareness rate across all hypertension surveys in Taiwan, we collaborated with the International Society of Hypertension to launch the MMM campaign. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. Over 1200 community pharmacies joined in this campaign, where participants were recruited to obtain BP measurements using automated oscillometric sphygmomanometers. Triplicate BP readings of right or left brachial artery were obtained after sitting for 10 min. A total of 52 514 individuals were screened during MMM17. After multiple imputation, 28 123 (53.8%) had hypertension. Of individuals not receiving antihypertensive medication, 5226 (17.8%) were hypertensive. Of individuals receiving antihypertensive medication, 8121 (35.7%) had uncontrolled BP. As compared with underweight individuals, adjusted systolic BP and diastolic BP raised by 6.1 and 4.1 mmHg, respectively, in overweight ones; while by 9.4 and 5.6 mmHg, respectively, in obese ones. May Measurement Month(MMM)17 was the largest BP screening campaign undertaken in Taiwan. The substantial numbers of unidentified and uncontrolled hypertensive patients, though lower than prior surveys in Taiwan, are challenging. Whether the continued MMM campaign would raise hypertension awareness at the national level awaits verification.